2021
DOI: 10.1108/jd-04-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Trace data visualisation enquiry: a methodological coupling for studying information practices in relation to information systems

Abstract: PurposeThe purpose of this paper is to examine whether and how a methodological coupling of visualisations of trace data and interview methods can be utilised for information practices studies.Design/methodology/approachTrace data visualisation enquiry is suggested as the coupling of visualising exported data from an information system and using these visualisations as basis for interview guides and elicitation in information practices research. The methodology is illustrated and applied through a small-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…The analysis drew on an information practices-oriented methodological coupling approach for spatially investigating trace data in relation to traditional ethnographically inclined methods (cf. Ekström, 2022bEkström, , 2022c. This approach enabled the investigation of how biodiversity citizen science information practices are enabled and constrained through material objects (Ekström, 2022b(Ekström, , 2022c) by zooming in and out of practice (Nicolini, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis drew on an information practices-oriented methodological coupling approach for spatially investigating trace data in relation to traditional ethnographically inclined methods (cf. Ekström, 2022bEkström, , 2022c. This approach enabled the investigation of how biodiversity citizen science information practices are enabled and constrained through material objects (Ekström, 2022b(Ekström, , 2022c) by zooming in and out of practice (Nicolini, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Ekström, 2022bEkström, , 2022c. This approach enabled the investigation of how biodiversity citizen science information practices are enabled and constrained through material objects (Ekström, 2022b(Ekström, , 2022c) by zooming in and out of practice (Nicolini, 2009). Comprising an abductive approach (cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2019, p. 9). Related, previous research has found that participants' in biodiversity citizen science gradually come to understand the importance of well-taken photographs for assisting species identification (Ekström, 2022b). These validation ambitions need further investigations in relation to the establishment of credibility and authority through information practices.…”
Section: Literature Reviewmentioning
confidence: 99%